Pengaruh Current Ratio dan Debt to Equity Ratio Terhadap Return On Asset Pada PT. Modernland Reality Tbk Periode 2012-2022 - Cristine Prestarika Lukito; Siti Nabila Nandini (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of the Curent Ratio and Debt To Equity Ratio on Return On Assets (case studies on real estate and property development companies listed on the IDX for the period 2012 - 2022). The results of research and data processing show that 1) Partially Curent Ratio has no significant effect on Return On Assets with a tcount of – 1,311 < ttable of 2,306 and a significant value of 0,226 > 0,05. 2) Partially, the Debt To Equity Ratio has a negative significant effect on Return On Assets with tcount – 2,868 > ttable 2,306 and a significant value of 0,021 <0,05. 3) simultaneously between Curent Ratio and Debt To Equity Ratio to Return On Assets there is no significant effect with a significant value of 0,057> 0,05 and Fcount value 4,181 <Ftable 4,46. And the value of the coefficient of determination is 51,1% while the rest is influenced by other variables.